AVAILABILITY BIAS AND MARKET EFFICIENCY IN PAKISTAN - SalehMemon, Muhammad; khan, Akmal; Sethar, Dr. Abdullah; Ali, Dr.Muhammad; Muhammad Shaikh, Dr.Faiz; Abbassi, Nusrat (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Market efficiency has been a kind of pivot both for academic research and for policymaking concerning stock market for the last decades. But this hypothesis recently keeps being criticized both from archival and survey strategy. In this paper we also criticized it based on psychological survey. Concretely we show that the appearance of availability bias has a possibility in real stock markets and we also demonstrate that even information efficiency is a kind of problem concerning human psychology. In this study we conclude that availability bias is a factor contributing in inefficiency of Pakistani market.